2017
DOI: 10.14763/2017.1.455
|View full text |Cite
|
Sign up to set email alerts
|

Towards responsive regulation of the Internet of Things: Australian perspectives

Abstract: The Internet of Things (IoT) is considered to be one of the most significant disruptive technologies of modern times, and promises to impact our lives in many positive ways. At the same time, its interactivity and interconnectivity poses significant challenges to privacy and data protection. Following an exploratory interpretive qualitative case study approach, we interviewed 14 active IoT users plus ten IoT designers/developers in Melbourne, Australia to explore their experiences and concerns about privacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
5
0
1
Order By: Relevance
“…This could encompass improved funding and resourcing for organisations such as the ACCC or the OAIC, which has received increased funding relating to its mandates regarding the Consumer Data Right and My Health Record (OAIC, 2021). Direct consumer and data protection standards for CIoTs could also be introduced that escalate to privacy‐based doctrines enforced through litigation (Richardson et al, 2017, p. 9), or co‐regulatory approaches where the design and enforcement of regulatory requirements are shared between a regulator and those being regulated (see Levi‐Faur, 2011a, 2011b). Moreover, Australia could consider approaches such as Europe's General Data Protection Regulation regime that provides a number of protections such as Article 22 that grants a right not to be subject to automated decision‐making or profiling that can occur from consumer IoT data (see also Mann and Matzner, 2019).…”
Section: Discussion: Implications For Future Regulatory Efforts In Au...mentioning
confidence: 99%
See 2 more Smart Citations
“…This could encompass improved funding and resourcing for organisations such as the ACCC or the OAIC, which has received increased funding relating to its mandates regarding the Consumer Data Right and My Health Record (OAIC, 2021). Direct consumer and data protection standards for CIoTs could also be introduced that escalate to privacy‐based doctrines enforced through litigation (Richardson et al, 2017, p. 9), or co‐regulatory approaches where the design and enforcement of regulatory requirements are shared between a regulator and those being regulated (see Levi‐Faur, 2011a, 2011b). Moreover, Australia could consider approaches such as Europe's General Data Protection Regulation regime that provides a number of protections such as Article 22 that grants a right not to be subject to automated decision‐making or profiling that can occur from consumer IoT data (see also Mann and Matzner, 2019).…”
Section: Discussion: Implications For Future Regulatory Efforts In Au...mentioning
confidence: 99%
“…In the context of regulating consumer IoT a responsive approach will mean escalating enforcement and the imposition of sanctions, starting with incentivising compliance through to more stringent responses backed by hard law and external investigation and enforcement. As Richardson et al (2017, p. 8) point out this could commence with self‐regulation through privacy‐by‐design initiatives ‘as a first and fairly minimal’ response to the regulation of CIoTs, by encouraging the adoption of privacy‐conscious design choices and offering clear customisable privacy settings and configurations to consumers. Organisations such as the IoTAA could assist with promoting privacy‐by‐design approaches and supporting such industry‐wide forms of self‐regulation.…”
Section: Discussion: Implications For Future Regulatory Efforts In Au...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the scenario of Medical grade IoT, it may require the attention of both departments [45]. On the other hand, some people believe strict government regulations may create additional bureaucracy and stifle the innovation and agility in the IoT development [49]. Several governments have already started to propose very basic level legislations to handle this trade-off.…”
Section: Regulatorsmentioning
confidence: 99%
“…Beyond IoT technical security challenges, many new legal and regulatory concerns are yet to be addressed. A study focusing on Australian perspectives discussed the impact of IoT-based ubiquitous surveillance on the basic structure of society [29] concluded that more efforts to reform a responsive regulation are required. In the United State (US), the Department for Homeland Security and Federal Trade Commission (FTC) have already promoted guidelines and best practices for IoT security based on frameworks and standards by the National Institute of Standards and Technology (NIST) but they are non-binding.…”
Section: Regulatory Landscapementioning
confidence: 99%